Correlation of surface pressure and hue of planarizable push–pull chromophores at the air/water interface - Neuhaus, Frederik; Zobi, Fabio; Brezesinski, Gerald; Dal Molin, Marta; Matile, Stefan; Zumbuehl, Andreas (Beilstein Journal of Organic Chemistry, 2017)
It is currently not possible to directly measure the lateral pressure of a biomembrane. Mechanoresponsive fluorescent probes are an elegant solution to this problem but it requires first the establishment of a direct correlation between the membrane surface pressure and the induced color change of the probe. Here, we analyze planarizable dithienothiophene push–pull probes in a monolayer at the air/water interface using fluorescence microscopy, grazing-incidence angle X-ray diffraction, and infrared reflection–absorption spectroscopy. An increase of the lateral membrane pressure leads to a well-packed layer of the ‘flipper’ mechanophores and a clear change in hue above 18 mN/m. The fluorescent probes had no influence on the measured isotherm of the natural phospholipid DPPC suggesting that the flippers probe the lateral membrane pressure without physically changing it. This makes the flipper probes a truly useful addition to the membrane probe toolbox.
Keywords: fluorescent probes; membrane biophysics; membrane pressure; membrane probes; monolayers

(untitled) - Chen, D.; Santore, M. M. (Langmuir, 2014)

(untitled) - Komura, S.; Shimokawa, N.; Andelman, D. (Langmuir, 2006)

(untitled) - Pliotas, C.; Dahl, A. C. E.; Rasmussen, T.; Mahendran, K. R.; Smith, T. K.; Marius, P.; Gault, J.; Banda, T.; Rasmussen, A.; Miller, S.; Robinson, C. V.; Bayley, H.; et al. (Nat. Struct. Mol. Biol., 2015)

(untitled) - Diz-Muñoz, A.; Fletcher, D. A.; Weiner, O. D. (Trends Cell Biol., 2013)

(untitled) - Traïkia, M.; Warschawski, D. E.; Lambert, O.; Rigaud, J.-L.; Devaux, P. F. (Biophys. J., 2002)

(untitled) - Fin, A.; Jentzsch, A. V.; Sakai, N.; Matile, S. (Angew. Chem., Int. Ed., 2012)

(untitled) - Doval, D. A.; Dal Molin, M.; Ward, S.; Fin, A.; Sakai, N.; Matile, S. (Chem. Sci., 2014)

(untitled) - Dal Molin, M.; Verolet, Q.; Colom, A.; Letrun, R.; Derivery, E.; Gonzalez-Gaitan, M.; Vauthey, E.; Roux, A.; Sakai, N.; Matile, S. (J. Am. Chem. Soc., 2015)

(untitled) - Soleimanpour, S.; Colom, A.; Derivery, E.; Gonzalez-Gaitan, M.; Roux, A.; Sakai, N.; Matile, S. (Chem. Commun., 2016)

The Structure of Biological Membranes - Lewis, R. N. A. H.; McElhaney, R. N. (The Mesomorphic Phase Behavior of Lipid Bilayers, 2012)

(untitled) - Brezesinski, G.; Möhwald, H. (Adv. Colloid Interface Sci., 2003)

(untitled) - Weinberger, A.; Tanasescu, R.; Stefaniu, C.; Fedotenko, I. A.; Favarger, F.; Ishikawa, T.; Brezesinski, G.; Marques, C. M.; Zumbuehl, A. (Langmuir, 2015)

(untitled) - Moehwald, H.; Brezesinski, G. (Langmuir, 2016)

(untitled) - Stefaniu, C.; Brezesinski, G.; Möhwald, H. (Adv. Colloid Interface Sci., 2014)

(untitled) - Stefaniu, C.; Brezesinski, G. (Adv. Colloid Interface Sci., 2014)

(untitled) - Stefaniu, C.; Brezesinski, G. (Curr. Opin. Colloid Interface Sci., 2014)

(untitled) - Levine, J. R.; Cohen, J. B.; Chung, Y. W.; Georgopoulos, P. (J. Appl. Crystallogr., 1989)

(untitled) - Chason, E.; Mayer, T. M. (Crit. Rev. Solid State Mater. Sci., 1997)

(untitled) - Mendelsohn, R.; Brauner, J. W.; Gericke, A. (Annu. Rev. Phys. Chem., 1995)

(untitled) - Vollhardt, D. (Curr. Opin. Colloid Interface Sci., 2014)

(untitled) - Shah, D. O.; Schulman, J. H. (J. Lipid Res., 1967)

(untitled) - Ziblat, R.; Leiserowitz, L.; Addadi, L. (J. Am. Chem. Soc., 2010)

(untitled) - Stefaniu, C.; Zaffalon, P.-L.; Carmine, A.; Verolet, Q.; Fernandez, S.; Wesolowski, T. A.; Brezesinski, G.; Zumbuehl, A. (Langmuir, 2015)

(untitled) - Blume, A. (Biochim. Biophys. Acta, 1979)

(untitled) - Marsh, D. (Biochim. Biophys. Acta, 1996)

(untitled) - Kim, J.; Swager, T. M. (Nature, 2001)

(untitled) - Flach, C. R.; Gericke, A.; Mendelsohn, R. (J. Phys. Chem. B, 1997)

(untitled) - Muenter, A. H.; Hentschel, J.; Börner, H. G.; Brezesinski, G. (Langmuir, 2008)

(untitled) - Schwieger, C.; Chen, B.; Tschierske, C.; Kressler, J.; Blume, A. (J. Phys. Chem. B, 2012)

(untitled) - Schrettl, S.; Stefaniu, C.; Schwieger, C.; Pasche, G.; Oveisi, E.; Fontana, Y.; Fontcuberta i Morral, A.; Reguera, J.; Petraglia, R.; Corminboeuf, C.; Brezesinski, G.; Frauenrath, H. (Nat. Chem., 2014)

(untitled) - Kuzmin, V. L.; Mikhailov, A. V. (Opt. Spectrosc., 1981)

(untitled) - Kuzmin, V. L.; Romanov, V. P.; Michailov, A. V. (Opt. Spectrosc., 1992)

(untitled) - Bertie, J. E.; Ahmed, M. K.; Eysel, H. H. (J. Phys. Chem., 1989)

(untitled) - Bertie, J. E.; Lan, Z. (Appl. Spectrosc., 1996)

(untitled) - Iyengar, S. S.; Frisch, M. J. (J. Chem. Phys., 2004)

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Hay, P. J.; Wadt, W. R. (J. Chem. Phys., 1985)

(untitled) - Wadt, W. R.; Hay, P. J. (J. Chem. Phys., 1985)

(untitled) - Hay, P. J.; Wadt, W. R. (J. Chem. Phys., 1985)